The Effects of Learning with Audiovisual Media and Learning Motivation on Learning Outcomes - Sipayung, April Yesaya; Rifki, Muhammad Sazeli; Naldi, Hendri (Indonesian Research Journal in Education |IRJE|, 2024)
This research aims to directly test the effect of one variable on another variable and test hypotheses regarding cause-and-effect relationships. This research is quantitative with a quasi-experiment design of 2x2 factorial by purposive sampling—the research sample comprised the 8th grade students of classes 1 and 2 (VIII.1 and VIII.2), with 32 students. The data are obtained through questionnaires. The results of the research show that (1) no significant difference between the learning outcomes of students in class 8 at SMPN 4 Kandis who are given gadget learning media and audiovisual media, (2) no interaction between learning media and learning motivation to the learning outcomes of students in class 8 at SMPN 4 Kandis with the analysis of two ways, 3) no significant difference between the learning outcomes of 8th grade students at SMPN 4 Kandis who are given gadget learning media and audiovisual media in groups of students with high learning motivation, (4) no significant difference between the learning outcomes of the 8th grade students at SMPN 4 Kandis who are given gadget learning media and students who are given audiovisual media in groups of students with low learning motivation.